Periodontal Status in Smokers and Nonsmokers: A Clinical, Microbiological, and Histopathological Study - Maddipati Sreedevi; Alampalli Ramesh; Chini Dwarakanath (International Journal of Dentistry)
A case-control study was done to assess the influence of smoking on clinical, microbiological, and histopathological parameters. Methods. Two hundred dentate male patients (100 smokers and 100 nonsmokers) ranging between 25 and 50 years were enrolled in the study. Periodontal parameters were recorded. Plaque samples were collected for microbial analysis for BANA test. Gingival biopsies were obtained from selected site for assessing histopathological changes. Results. Both groups showed almost similar plaque levels (P=0.258), but smokers had reduced gingival (0.62 ± 0.31) and bleeding indices (28.53 ± 17.52) and an increased calculus index (1.62 ± 0.36). Smokers had an increased probing depth of 4–7 mm (P=0.009) and overall increased CAL. No difference in microbiota was found between the two groups. Histopathologically smokers showed a decreased blood vessel density (8.84 ± 0.96) and inflammatory cells (52.00 ± 9.79). Conclusions. It is quite possible that many of the pathogenic mechanisms involved in tissue degradation in periodontitis in smokers could be quite different from those in nonsmokers.